BEST-MS: A prospective head-to-head comparative study of natalizumab and fingolimod in active relapsing MS. (September 2021) - Cohen, Mikael; Mondot, Lydiane; Bucciarelli, Florence; Pignolet, Béatrice; Laplaud, David-Axel; Wiertlewski, Sandrine; Brochet, Bruno; Ruet, Aurélie; Defer, Gilles; Derache, Nathalie; Vermersch, Patrick; Zephir, Hélène; et al.
Background: There are few head-to-head studies to compare highly active treatments in multiple sclerosis (MS) Objective: The aim of this study was to compare the effectiveness between natalizumab (NTZ) and fingolimod (FTY) in active relapsing–remitting MS Method: Best Escalation STrategy in Multiple Sclerosis (BEST-MS) is a multicentric, prospective study with a 12-month follow-up including patients with active MS. Treatment choice was at the discretion of physician. Clinical and magnetic resonance imaging (MRI) data were collected at baseline and at 12 months. The primary outcome was the proportion of patients reaching no evidence of disease activity (NEDA) at 12 months. Secondary outcomes included annualized relapse rate and MRI activity. Results: A total of 223 patients were included (NTZ: 109 and FTY: 114). Treatment groups were well balanced at baseline. Proportion of NEDA patients was 47.8% in NTZ group versus 30.4% in FTY group ( p = 0.015). This superiority was driven by annualized relapse rate and MRI activity. In the multivariate analysis, treatment group was the only factor associated with NEDA at 12 months with a lower probability in FTY group (odds ratio (OR) = 0.49, p = 0.029). Conclusion: BEST-MS is a prospective study that compared head-to-head the effectiveness of NTZ and FTY in active relapsing–remitting MS. Our results suggest a superiority of NTZ over FTY.